Al-Ma’na al-Tarabuthi fi Riwayati Mauti Ma’ali al-Wazir Nawal El-Sa’dawi ‘ala Asasi Nadzariyyati Geoffrey Leech - Fasky Randika; Abdul Basid (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
This study investigates the associative meanings found in Nawal El-Sa'dawi's novel Mautu Maʿālī al-Wazīr with the aim of enriching semantic studies, particularly those related to associative meaning in Arabic literary texts. The research seeks to identify and classify the associative meanings embedded in words and phrases throughout the novel based on Geoffrey Leech's theory of meaning. This study employed a qualitative descriptive approach using library research. The primary source of data was the novel Mautu Maʿālī al-Wazīr, published in 2005, consisting of 72 pages. Data were collected through intensive reading and note-taking techniques, while data analysis followed three stages: data reduction, data display, and conclusion drawing. The findings reveal a total of 43 instances of associative meaning distributed across five categories proposed by Leech. These include stylistic meaning (4 data), affective meaning (11 data), collocative meaning (12 data), connotative meaning (15 data), and reflective meaning (1 datum). Among these categories, connotative meaning appears most frequently, indicating the author's extensive use of figurative and context-dependent expressions to convey deeper social and emotional messages. The results demonstrate that associative meaning plays a significant role in shaping the literary style and semantic richness of the novel, highlighting the importance of semantic analysis in understanding Arabic literary discourse.